2021
DOI: 10.15560/17.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

A ghost in the mist: extension of the known range of Colombian Weasel, Neogale felipei (Izor & de la Torre, 1978) (Carnivora, Mustelidae), in the Cordillera Occidental

Abstract: The Colombian weasel, Neogale felipei (Izor & de la Torre, 1978), is one of the most enigmatic and threatened carnivores in South America, with only six confirmed records in the Andes of Ecuador and Colombia. During a long-term trail camera survey conducted at Mesenia-Paramillo Natural Reserve, we recorded the northernmost occurrence of the species, which extends its distribution by approximately 120 km to the north from the nearest previously known locality in Colombia. We also provide some comments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…1), although several studies targeted multiple species simultaneously. There were very few (n < 3) studies on Asian weasel species Mustela altaica, Mustela itatsi and Mustela strigidorsa, and no studies on weasel species endemic to Africa or South America (although see Cepeda-Duque et al 2023, published after our literature search). Most studies used methods to estimate species presence or to assess distribution (45%), followed by estimating relative abundance (44%), and species occupancy and/or detection probability (11%).…”
Section: Breadth Of Non-invasive Weasel Monitoring Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…1), although several studies targeted multiple species simultaneously. There were very few (n < 3) studies on Asian weasel species Mustela altaica, Mustela itatsi and Mustela strigidorsa, and no studies on weasel species endemic to Africa or South America (although see Cepeda-Duque et al 2023, published after our literature search). Most studies used methods to estimate species presence or to assess distribution (45%), followed by estimating relative abundance (44%), and species occupancy and/or detection probability (11%).…”
Section: Breadth Of Non-invasive Weasel Monitoring Techniquesmentioning
confidence: 99%
“…Other studies adopted similar camera trap designs, such as foldable plastic boxes for weasels and stoats at high altitudes in Spain (Fig. 5; Salvador et al 2022) and metal boxes for long-tailed weasel and Colombian weasel Neogale felipei in Colombia (Cepeda-Duque et al 2023). Another boxed camera trap, developed to monitor small mammals under snow (Soininen et al 2015), has shown success in detecting Mustela nivalis nivalis and Mustela erminea in arctic systems (Kleiven et al 2023).…”
Section: History Of Developmentmentioning
confidence: 99%
See 2 more Smart Citations